A comparative analysis in monitoring 24-hour urinary copper in wilson disease: sampling on or off treatment? - Isabelle Mohr; Patrick Lamade; Christophe Weber; Viola Leidner; Sebastian Köhrer; Alexander Olkus; Matthias Lang; Andrea Langel; Patrischia Dankert; Melanie Greibich; Silke Wolf; Holger Zimmer; et al. (Orphanet Journal of Rare Diseases)
Abstract Background & Aim Twenty-four-hour urinary copper excretion (24 h-UCE) is the standard diagnostic tool for dose adjustments in maintenance therapy in Wilson disease (WD) patients. Guidelines lack data if both variants of 24 h-UCE measurement (with or without 48 h of treatment interruption) are equally interpretable. Methods Eighty-four patients with a confirmed diagnosis of WD treated with chelators (50% of patients with D-Penicillamine and 50% with trientine) and with pairwise 24-h-UCE values on-therapy and off-therapy were included in the analysis. Pairwise urinary sampling between October 2022 (T0) and a 12-month FU (T2) was compared, and exchangeable copper (CuEXC) was additionally measured at T0. Results Among the 84 patients, 65% had predominant hepatic symptoms, the median age was 42 years, and 58% were female. At T0, patients were in the stable maintenance phase, with a median treatment duration of 21.9 years. The levels of the biochemical markers liver and copper metabolism remained stable over the 12-month observation period for all patients. 24 h-UCE off-therapy significantly decreased from T0 to T2 (p = 0.03), whereas no statistically significant differences were detected for 24 h-UCE after therapy. Both sampling methods did not correlate. CuEXC was significantly correlated with 24 h-UCE after 48 h of dose interruption (p = 0.018) but not with 24 h-UCE after therapy. A total of 46% of the 24 h-UCE value pairs were discordant, laying out the aimed therapeutic ranges given in current international guidelines. Conclusion Off-therapy 24 h-UCE reflects the “free” copper pool more accurately than does urinary sampling. The study shows discordant results for both sampling methods in approximately half of the patients, revealing that interpretation of 24 h-UCE with respect to chelator-dosing decisions should be performed with caution.